Manfaat Keasaman Yoghurt dalam Pencegahan Karies Gigi - Sugiaman, Vinna Kurniawati (Zenit, 2014)
Dental caries is a dental and oral health problem that is dominant in our country regardless of age, race, or the state of the economy. Therefore, we need to have a preventive measure to reduce the caries index that aims to enhance the standard of living by extending the usefulness of the teeth in the mouth.One of the actions to prevent the formation of dental caries is consuming yoghurt that contains probiotics and has the ability to improve the overall body health and oral health, such as dental caries, periodontitis, and halitosis.Probiotics can prevent and reduce the occurance of dental caries that works directly on the Streptococcus mutans as cariogenic bacteria to prevent its growth through several mechanisms that produce antimicrobial substances, bound in the oral cavity, immunomodulatory, and modify the conditions of the oral cavity. With a preventive action against dental caries,it is expected that in the future the classical problems of oral health such as dental caries is just a history.Keywords: dental caries, preventif, yoghurt